»Ko bi le dobili dovoljenje za stalno prebivanje« - Fidler, Katja (Socialno delo, 2025)
The interaction of migration laws with laws on citizenship, the labor market, and social welfare in the everyday lives of migrants from third countries working in Slovenia as low-skilled workers, functions as a mechanism of structural violence. Etnographic descriptions of processes of renewal of residence permits and access to social rights of four families illustrate this indirect violence, embedded in the functioning of institutions and society as a whole. Findings from ethnographic material show how migrants struggle to meet their basic needs due to the legally prescribed uncertainty of temporary residence permits, the chain dependency of residence and social rights, and the lack of societal support. The conditionality and temporariness of their legal status place them in a subordinate and precarious position which deterioates their health. The article concludes with some practical proposals to reduce such violence.
Keywords: advocacy; državljani tretjih držav; migracijska politika; migrants; migration policy; pravice; priseljenci; social rights; social security; socialno varstvo; third country nationals; zagovorništvo